Model-based climate change adaptational potential and productivity of some cowpea genotypes and its sensitivity to bias adjustment - Adusei, Grace; Aidoo, Moses Kwame; Srivastava, Amit Kumar; Asibuo, James Yaw; Gaiser, Thomas (Frontiers in Agronomy, 2023)
Grain legumes are essential for the protein supply to an ever-growing population in Africa. However, little is known about the adaptive capacity of major grain legumes under future climatic change for the evaluation of climate change impact and adaptation. This study assessed the adaptation potential of some cowpea genotypes to future climate change in the moist (Kumasi-Ghana) and dry savanna (Ouagadougou-Burkina Faso) biomes of West Africa based on a validated process-based cowpea crop model using the output of four GCMs (Global Circulation Models) for two Shared Socio-economic Pathways (SSPs i.e., ssp126 and 585). In addition, it assesses the sensitivity of the cowpea model to bias-corrections of the GCM outputs. In comparison of future socio-economic pathways with historic time series, the use of bias-corrected climate model output slightly increased the rate of the phenological development of the genotypes in the future period except in Ouagadougou, in the ssp585 scenario. Without bias correction, this increase of the rate of phenological development in the future scenarios was less pronounced. With bias correction, the total aboveground biomass and yield of all genotypes were reduced in both shared socio-economic pathways. The change in the average water stress and phosphorous stress were genotype specific. Despite a general yield decline in both SSPs, the genotypes Asontem and GH6060 exhibited the adaptational potential to future climate change in the moist and dry savanna biomes. This is by higher accumulation of total aboveground biomass, higher yield, and tolerance to high temperature as well as high water use and photosynthetic efficiency due to higher atmospheric CO2 concentrations, despite faster phenological development.